Menumbuhkan Kinerja MLM Melalui Promosi Penjualan dan Orientasi Smart-Working - Susilowati, Luky (Jurnal Riset Ekonomi dan Bisnis, 2008)
In the Multi Level Marketing Firm the basic strategy to find success are try to build the profesional distributor, smart, hardworking.  These policy must  be priority for higher sales omzet.  The aim of this research to analyze Sales Promotion and Smart-working Orientation influence to Sales Performance in MLM Executive Diamond Director PT. Harmoni Dinamik–High Desert in Surabaya. Population of this research are all of distributors PT. Harmoni Dinamik–High Desert in Surabaya. Purposive sampling has been taken to identify the sample, there are down line MLM Executive Diamond Director, who has Job Performance that’s measure by Business Point (≥ 100 BP). These data analyzed by SEM approach through AMOS program. The result of this research show that; there is positive influence of sales promotion factor to Sales Performance and Smart-Working Orientation factor influential positive to Sales Performance.  Keywords : Sales Promotion, Smart-Working Orientation, Sales Performance